Modelagem numérica de diagonais equivalentes em painéis de cisalhamento do sistema Light Steel Framing - Rodrigo Oliveira Vitor (2012)
This paper presents a study regarding the structural stability of Shear Wall of the Light Steel Framing System (LSF). The construction system named LSF, also known as selfsupporting steel dry construction system, has been consolidated in the Brazilian civil construction. This system consists of frame galvanized steel cold-formed profiles that works with panels, providing self-supporting structure. The frames are composed of slender structural members, named track and stud. The wall bracing can be made using Oriented Strand Board (OSB) or cementitious board, both have considerable mechanical strength, or gypsum board, that only has sealing function. The numerical model is based on the Finite Elements Method, running on the software ABAQUS. Through the evaluation of the obtained results, it is proposed an analytical model for the equivalent diagonal and an equation based on the nonlinear regression to represent the model in a general way. Thus, the frame structural analysis with shear wall can be performed without the structural board, but with a circular cross-section fictitious bracing member working under tensile stress (Equivalent Diagonal).